Studio to manage labor accident prevention in mine Uchucchacua - Rodríguez Vigo, Carlos (2012)
This research seeks to understand the reasons that influence accident in Uchucchacua mine, which has a high occurrence of accidents in recent years . The research aims to follow a methodology to recognize hazards and critical risks facing the unit , in order to take measures of successful control. This involves determining those few characteristics of the staff and the work that influenced the greater proportion of the results , using the Pareto Principle . Indicated it is possible to analyze the statistics derived from accident investigation reports . After having evaluated 100 % of accidents in the last three years was identified that there are five types of accidents resulting in 79 % of accidents , five are the dangers for substandard acts that generated 83% of accidents, which in turn generate 86% of the factors registered jobs . It was also established that six hazards substandard conditions that generated 80% of accidents, influencing 88% of the work factors that contributed to their occurrence.